Pengaruh Strategi Writing in the Here and Now terhadap Keterampilan Menulis Puisi Kelas X - Nurafifah, Alya Nazmi; Triyadi, Slamet; Mujtaba, Sahlan (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Students' interest in taking part in writing lessons at school is still low because there are no learning strategies implemented by teachers when writing lessons take place. This study aims to determine the effect of Writing In The Here And Now Technique on poetry writing skills for class X students SMKN 1 Karawang Two samples were employed, the experimental class (X TP 3) and control class (X TPFL 2). There is a pretest and posttest to determine student learning outcomes. Data processed using the SPSS Statistics Version 27 application shows that the experimental and control classes have different learning outcomes. The average in the experimental class was 79.11 and the control class was 63.08. Based on these averages, it can be concluded that there was a significant increase in learning outcomes in the experimental class.